Middle East and North Africa : Economic Outlook and Key Challenges. (Policy Papers; Policy Paper ;, 2012)
Historic transitions in the Arab Spring countries are coming under increasing strain frommacroeconomic pressures and unmet social demands. Domestic uncertainty over the countries' future course, compounded by the global slowdown and rising oil prices, took a toll on growth during 2011. The outlook for 2012 and 2013 is equally challenging. The protracted political transition, lower global growth, and euro zone weakness are likely to result in a slow and drawn-out economic recovery, with unemployment at best stabilizing at high levels. Maintaining macroeconomic stability in this environment will be challenging, not least since policy buffers were reduced during 2011. Indeed, gross external and fiscal financing needs of MENA oilimporters are projected at about USD 93 and USD 103 billion, respectively, in 2012-13. With capital markets expected to provide only a small part of these funds, official financial support will be essential to allow countries to continue on their path toward economic transformation. But at the same time, countries need to make tangible progress on that path. This requires bold reform and modernization agendas that command broad consensus and are embedded in a sustainable medium-term macroeconomic policy framework to build confidence, anchor expectations, and pave the way for sustained and inclusive growth.